Pengaruh Kemampuan Keuangan dan Posisi Fiskal Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Kalimantan Barat - Ariza, Anggatia (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
The implementation of local autonomy and decentralization empowers the local government tomanage their own area largely and properly. The research aims to examine the financial andfiscal position and their effects towards the economic growth of the regencies or cities in WestKalimantan. Moreover, the1 financial capability is proxied by the proportion of PDS while thefiscal position is determined by the direct expenditure per capita to verify their effects to theeconomic growth. This research, furthermore, utilizes the panel data from 12 regencies/citiesthroughout West Kalimantan in 2006-2010 and used Fixed Effects Method. As a result, theproportion of PDS affects negatively and significantly the economic growth, while the directexpenditure per capita has slightly a negative effect towards the economic growth ofregencies/cities in West Kalimantan.